Effect of coupling phase change materials and heat pipe on performance enhancement of Li‐ion battery thermal management system. (3rd November 2020) - Yuan, Qiuqi; Xu, Xiaoming; Tong, Guangyao; Ding, Hua
Summary: A thermal management system (TMS) including heat pipes, heat‐conducting glue, phase change materials (PCM), and micro‐channel plates is built in this research. The heat pipes and heat‐conducting glue can solve the problem of poor thermal conductivity and large internal temperature difference ( T d ) of TMS including PCM and liquid cooling. The micro‐channel plates can solve the problem that TMS combined with the PCM and the heat pipes is difficult to transfer heat. The designed TMS can cool and heat li‐ion battery. Through the li‐ion battery discharge test experiment by 1C, 2C, and 3C, the li‐ion battery heating power is obtained. The temperature change curve of li‐ion batteries at 1C, 2C, 3C discharge and when ambient temperature ( T a ) is −20°C, −10°C, 0°C, and 20°C are studied. When the T a is lower than 0°C, the designed TMS can heat the li‐ion battery to 20°C, and make the T d inside the li‐ion batteries approach 0°C within a short period.